Physical Activity and Its Technology in Patients with Chronic Disease - Budi Santoso (HM Publisher, 2016)
Non-Communicable Diseases (NCD) has a high mortality rate. This disease is closely related to an unhealthy lifestyle, including nutritional intake, physical activity, consumption of alcohol and cigarettes. Regular physical activity can increase the chances of living longer by lowering the risk of chronic disease. Pedometer is a technology that can be used to assess and motivate physical activity behavior.